Evaluasi Kebijakan Publik: Tinjauan Literatur Sistematis Kritis tentang Metodologi, Tren dan Kesenjangan, serta Peluang Masa Depan - Rizki Ananda; Umanto Umanto (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2025)
This study conducts a systematic literature review of recent developments in policy and program evaluation from 2015 to 2023, examining methods, approaches, challenges, and future research directions. Following PRISMA guidelines, a search of the Scopus and Science Direct databases yielded 58 relevant articles. Key findings indicate a shift towards mixed-methods approaches, agent-based simulation, and stated preference techniques, although studies predominantly originate from developed countries and focus on social, environmental, and health issues. Bibliometric analysis shows that 62.9% of the articles appeared in Scopus Q1 journals. Evaluation effectiveness is significantly influenced by internal factors (e.g., program design, data quality) and external factors (e.g., political context, financial support). While evaluations impact decision-making and policy improvement, challenges remain in utilizing and generalizing results. Crucially, this review identifies gaps, including methodological limitations, a scarcity of studies on vulnerable groups, and a lack of standardized indicators. This study contributes to the advancement of policy evaluation methodologies by, for example, highlighting the need for strategic integration of qualitative and quantitative data within mixed-methods designs, going beyond mere combination to achieve nuanced understanding. It also emphasizes the critical importance of adapting systems thinking approaches, using for example, process tracing and agent-based modelling to specific developing country contexts, providing a pathway for more relevant and impactful evaluations. This research underscores the need for participatory, adaptive, and evidence-focused evaluation approaches that explicitly consider causal mechanisms, and recommends a concerted effort to develop comprehensive mixed-methods research, prioritize studies in developing countries, and build capacity for implementing these advanced methodologies.